Perancangan Sistem Pemantauan Kelembaban Tanah,Udara dan Suhu pada Tanaman Bawang Merah Menggunakan IoT - Muh. Agus; Putri Ayu Maharani; Mardhiyyah Rafrin (Prosiding SISFOTEK, 2023)
Shallots are one of the abundant horticultural commodities in Enrekang Regency. Even though the harvest of this plant is abundant, most of the cultivation in this area is still done manually. One of the systems that farmers need most at the moment is a plant watering system, because farmers have to maximize crop yields where the watering process is still done manually using sprinklers. Therefore, this research aims to design a monitoring system using IoT technology based on the parameters of temperature, soil humidity and air humidity. There are 3 components that will be built, namely IoT technology to collect data in real time, a web-based database application to process and store data, and a mobile application for monitoring. This research will be carried out in 4 stages: 1) preparation and coordination, 2) design and installation of tools and data collection, 3) application design, 4) publication. There are 4 control system points embedded in the fields and connected to each other with a Wireless Sensor Network system which continuously reads values from sensors. Then data from the sensor will be forwarded by the NodeMCU EPS8266 module to the firebase.com database and then displayed in the Mobile Application. The NodeMCU ESP8266 module can send data if it is connected to a Wi-Fi access point signal with a range of ±25 meters and the waiting time (delay) of the NodeMCU ESP8266 module will be greater the further the distance from the Wi-Fi access point.